Dengue virus disease : from origin to outbreak - Qureshi, Adnan I.; Saeed, Omar (Academic Press, 2020)
"[This book] provides a detailed accounting of one of the world's fastest growing infections. According to the World Health Organization, Dengue virus incidence has increased 30-fold over the past 50 years, with up to 50 to 100 million infections occurring annually in over 100 endemic countries. This estimate puts nearly half the world's population at risk. This book reviews the history, clinical and diagnostic aspects of dengue virus, also presenting our current knowledge on the pathophysiology of severe dengue and addressing the importance of dengue virus infections in those traveling to parts of the world where it is endemic."--Website publisher